2020
DOI: 10.3390/cells9071730
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Function and Clinical Role of Thyroid Stimulating Hormone Receptor in Cancer Cells

Abstract: The thyroid stimulating hormone (TSH) and its cognate receptor (TSHR) are of crucial importance for thyrocytes to proliferate and exert their functions. Although TSHR is predominantly expressed in thyrocytes, several studies have revealed that functional TSHR can also be detected in many extra-thyroid tissues, such as primary ovarian and hepatic tissues as well as their corresponding malignancies. Recent advances in cancer biology further raise the possibility of utilizing TSH and/or TSHR as a therapeutic targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 136 publications
(159 reference statements)
0
31
0
Order By: Relevance
“…Besides TSH that activates TSHR there are a lot of other mutations happening in the TSHR gene, that could be germline or tumor specific mutations and could trigger automatically cascades and therefore encourage cell proliferation, like V509A, C672Y and M453T. Meaning that TSHR has a somehow oncogenic role in TC but to develop into a proper malignancy there should be also other existing mutations ( 46 , 47 ). In a study it was showed that there were TSHR in normal breast tissue and its expression was increased in breast tumors but further studies need to be done to confirm the exact role of TSHR in breast malignancies ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides TSH that activates TSHR there are a lot of other mutations happening in the TSHR gene, that could be germline or tumor specific mutations and could trigger automatically cascades and therefore encourage cell proliferation, like V509A, C672Y and M453T. Meaning that TSHR has a somehow oncogenic role in TC but to develop into a proper malignancy there should be also other existing mutations ( 46 , 47 ). In a study it was showed that there were TSHR in normal breast tissue and its expression was increased in breast tumors but further studies need to be done to confirm the exact role of TSHR in breast malignancies ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have revealed that the macrobian population is characterized by high TSH generation and TSH insensitivity without altered energy metabolism [ 124 , 125 ]. Moreover, TSH can reverse aging mediated by BRAFV600E mutations in mice, both in vitro and in vivo [ 126 ]. Similar to GH, insulin/insulin-like growth factor I signaling suppression delayed stress granule protein accumulation and subsequently prolonged longevity in C. elegans [ 127 , 128 ].…”
Section: Endocrine Hormones May Delay Aging But Promote Cancermentioning
confidence: 99%
“…TSHR is a protein of 87 kDa and belongs to the family of G-coupled protein receptors (GCPRs) [68]. The activation of TSHR in the plasma cell membrane transmits signals through G proteins Gas and Gaq, and downstream through the cAMP/PKA/CREB pathway and the phospholipase C/PI3K/AKT/mTOR pathway.…”
Section: Expression Of Trs Tshr and Related Proteins In Human Breast ...mentioning
confidence: 99%
“…The role of TSHR is established in well-differentiated thyroid cancers, where treatment with T4 to suppress TSH secretion from the hypophysis, in order to prevent TSHR activation, is the mainstay of treatment [69]. TSHR is also expressed in other cancers, such as ovarian carcinomas, hepatomas and melanomas [68,[70][71][72]. The expression of TSHR is increased in breast cancer tissues compared to adjacent normal mammary tissues [73].…”
Section: Expression Of Trs Tshr and Related Proteins In Human Breast ...mentioning
confidence: 99%